Metagenomics at the interface of diagnostics and surveillance: a near-term perspective (One Health & Risk Management, 2025)
The global landscape of infectious diseases is undergoing rapid and profound change. Increased human mobility, climate-driven shifts in vector ecology, intensified human-animal-environment interactions, and geopolitical instability have collectively amplified the risk of emerging and re-emerging infectious diseases. At the same time, public health systems are increasingly confronted with pathogens that are unexpected, genetically diverse, or poorly represented in existing diagnostic panels. These developments highlight the growing limitations of exclusively targeted diagnostic approaches and underscore the need for broader, more adaptive tools.In this context, metagenomic sequencing has emerged as a transformative technology. By enabling unbiased detection and genomic characterization of pathogens directly from clinical, environmental, or animal samples, metagenomics offers capabilities that extend far beyond conventional diagnostics. While historically confined to research and outbreak investigations, metagenomics is now approaching a level of maturity that warrants serious consideration for integration into routine diagnostics and risk-oriented surveillance frameworks.Metagenomic sequencing is no longer a distant prospect but a rapidly maturing technology with tangible relevance for routine diagnostics and high-risk disease surveillance. While targeted assays will continue to form the backbone of diagnostic testing, metagenomics offers unparalleled breadth and genomic resolution, enabling detection and characterization of pathogens that would otherwise remain undetectable.The near future of diagnostics will be defined not by the replacement of existing methods, but by their intelligent integration. By combining targeted testing with selective metagenomic analysis, public health systems can enhance preparedness, improve outbreak response, and strengthen biosafety and biosecurity in an increasingly complex global health landscape.